Working-Posture Analysis on Workers at Bagging Sector of Urea Fertilizer I in PT Pupuk Sriwidjaja Palembang - Diga Areta; Desheila Andarini (Perhimpunan Ergonomi Indonesia, 2021)
Part of Occupational Safety and Health was the ergonomics aspect. Ergonomics has a strong correlation with work-postures and manual handling activities. Improper work postures and heavy manual handling are risk factors for the development of musculoskeletal disorders. The aims of this research were assessing ergonomic risk with work-posture analysis on workers at the bagging sector of urea fertilizer I in PT Pupuk Sriwidjaja Palembang using Quick Exposure Check (QEC) to describe the risk for musculoskeletal disorders. The method of this research was descriptive and qualitative. Informants in this study amounted to 1 key informant from the bagging sector of urea fertilizer I department and 1 key informant from industrial hygiene and health department then 12 informants from bagging sector workers with 3 people working for> 10 years, 7 people working for 5-10 years and 2 people working for <5 years. Ergonomics risk assessment uses Quick Exposure Check (QEC). Quick Exposure Check (QEC) was designed to assess the exposures of risk factors for musculoskeletal disorders in workers. Work posture of filling the fertilizer bag and cutting the yarn had an average exposure score of 88.5% then tidying up the fertilizer bag and sewing the fertilizer bag got 87% and placing the fertilizer bag to pallet was 91.4%. All of the postures in the bagging sector of urea fertilizer I in PT Pupuk Sriwidjaja Palembang had exposure scores above 70% which are included in action level 4. So based on the result, it needs to be investigated and changed immediately on work posture to reduce ergonomic risks and prevent musculoskeletal disorders.